2020
DOI: 10.1101/2020.04.30.20086108
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A clinical and biological framework on the role of visceral fat tissue and leptin in SARS-CoV-2 infection related respiratory failure

Abstract: Obesity is a risk factor for SARS-CoV-2 infected patients to develop respiratory failure. Leptin produced in visceral fat might play a role in the deterioration to mechanical ventilation. A cross sectional study was performed. The mean BMI was 31 kg/m 2 (range 24.8 -48.4) for the 31 SARS-CoV-2 ventilated patients and 26 kg/m 2 (range 22.4-33.5) for the 8 controls. SARS-CoV-2 infected patients with a similar BMI as control patients appear to have significantly higher levels of serum leptin. The mean leptin leve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…However, the paper of van der Poort et al (2020) found that patients that have an increased Body Mass Index (BMI) also have increased leptin levels in serum, which they hypothesize could correlate with severity of the infection [ 195 , 196 ]. Interestingly, increased expression of the ACE2 receptor in the lung epithelia are positively correlated with obesity, indicating that obese individuals might be at higher risk for SARS-CoV-2 infection [ 195 , 196 ]. In conclusion, there is no robust evidence to either demonstrate or exclude that skin and adipose tissue harbor SARS-CoV-2 viral particles.…”
Section: Resultsmentioning
confidence: 99%
“…However, the paper of van der Poort et al (2020) found that patients that have an increased Body Mass Index (BMI) also have increased leptin levels in serum, which they hypothesize could correlate with severity of the infection [ 195 , 196 ]. Interestingly, increased expression of the ACE2 receptor in the lung epithelia are positively correlated with obesity, indicating that obese individuals might be at higher risk for SARS-CoV-2 infection [ 195 , 196 ]. In conclusion, there is no robust evidence to either demonstrate or exclude that skin and adipose tissue harbor SARS-CoV-2 viral particles.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, high leptin levels have been associated with accumulation of alveolar fluid and increased inflammation upon hypoxia and ARDS [58]. Therefore, it may be hypothesised that excess visceral adipose tissue in patients with COVID-19 may drive disease progressionwhether or not affected by genderespecially through aggravating the cascade of hyperinflammatory reactions in the disease [59]. Ultimately, this 'cytokine storm' may lead to multiple organ failure in patients with COVID-19.…”
Section: Obesitymentioning
confidence: 99%
“…и др. Дисбаланс адипокинов и его роль в патогенезе новой коронавирусной тием дыхательной недостаточности, потребностью в ИВЛ и летальностью) была подтверждена целым рядом независимых исследований, проведенных в разных странах [31][32][33]. Метаанализ нескольких крупномасштабных эпидемиологических исследований свидетельствует о том, что с увеличением массы тела значительно возрастает и тяжесть заболевания [34][35][36].…”
Section: ожирение и нкиunclassified